2021
DOI: 10.3390/math9212656
|View full text |Cite
|
Sign up to set email alerts
|

A Climate-Mathematical Clustering of Rainfall Stations in the Río Bravo-San Juan Basin (Mexico) by Using the Higuchi Fractal Dimension and the Hurst Exponent

Abstract: When conducting an analysis of nature’s time series, such as meteorological ones, an important matter is a long-range dependence to quantify the global behavior of the series and connect it with other physical characteristics of the region of study. In this paper, we applied the Higuchi fractal dimension and the Hurst exponent (rescaled range) to quantify the relative trend underlying the time series of historical data from 17 of the 34 weather stations located in the Río Bravo-San Juan Basin, Mexico; these da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The Hurst exponent method [36] gives an estimation of a time series autocorrelation and it is a powerful tool to study persistence and long-range dependence [37,38]. It is widely used in many research fields, from climate science [39][40][41][42] to hydrology and water resources [38,43,44] and economics [35,45]. In this research, the rescaled range (R/S) analysis [36] provides the estimation of the Hurst exponent.…”
Section: Hurst Exponentmentioning
confidence: 99%
“…The Hurst exponent method [36] gives an estimation of a time series autocorrelation and it is a powerful tool to study persistence and long-range dependence [37,38]. It is widely used in many research fields, from climate science [39][40][41][42] to hydrology and water resources [38,43,44] and economics [35,45]. In this research, the rescaled range (R/S) analysis [36] provides the estimation of the Hurst exponent.…”
Section: Hurst Exponentmentioning
confidence: 99%
“…(2020); Adarsh and Priya (2021); Benavides‐Bravo et al. (2021); Dimitriadis, Iliopoulou, et al. (2021); Dimitriadis, Koutsoyiannis, et al.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Hurst has been used to characterize LTP across multiple disciplines, ranging from climate science to the analysis of internet traffic and the flow of blood in human arteries (O'Connell et al, 2016). Recent research on Hurst behavior in the climate and hydrology fields is reported by Adarsh et al (2020); Adarsh and Priya (2021); Benavides-Bravo et al (2021); ; ; Legates and Outcalt (2022); Pal et al (2020); Rahmani and Fattahi (2021, 2022c, 2022a, 2022b. The hypothesis of long-term persistence (LTP) in annual precipitation has been explored in a number of studies of point and grid scale data.…”
mentioning
confidence: 99%
“…Additionally, Nikolopoulos et al [23] used the HFD algorithm to study PM 10 time series, indicating fractality and long-term memory in the behavior of the records from the studied stations. However, none of these exponents have been calculated to compare them with geographic parameters, such as latitude, longitude, and altitude, despite the fact that those relations have been found for other meteorological variables [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%